Effectiveness of Environmental Policy Enforcement and The Impact by Industrial Mining, Energy, Mineral, And Gas Activities In Indonesia - Hidjaz, Kamal (International Journal of Energy Economics and Policy, 2019)
They are being polemic for Indonesia between implementing production and sustainability simultaneously, considering that Indonesia is a newly emerging country, which of course wants to be independent and also sovereign from the regional side as a unitary state and even financially independent to meet all the needs of the Indonesian people. The main challenge faced by Indonesia is pursuing maximum economic growth through the use of natural resources. The effectiveness of environmental law enforcement on the activities of the mining, gas, and mineral industry can run smoothly and smoothly concerning several fundamental aspects. On the other hand, mining activity is an effort to create jobs, improve the economy, which aims at equitable distribution of income through the absorption of labor in the sector of the mining industry. Environmental issues that are becoming a global issue require the government to take firm action against violators/perpetrators of environmental pollution to cause deterrent effects for others. The government can take legal steps through administrative, criminal, and civil considerations as a manifestation of creating environmentally friendly and sustainable production activities in the future. Keywords: Environmental Policy, Environmental Law, Socio-Legal Research. JEL Classifications: O44, Q5, Q56 DOI: https://doi.org/10.32479/ijeep.8146